Proceeding of 1999- Workshop on MHD Computations Study on numerical methods related to plasma confinement - Workshop on MHD Computations Study on Numerical Methods related to Plasma Confinement (1999 : Toki, Japan); T. Kako; T. Watanabe; National Institute for Fusion Science (Nagoya, Japan : NIFS, 2000)
PSZJBL